IMPROVING LEARNING OUTCOMES OF FIFTH GRADE STUDENTS ON THE SCIENCE LESSON OF LIGHT MATERIAL AND ITS PROPERTIES THROUGH APPLICATION OF DEMONSTRATION LEARNING MODELS - Ahmad Amas Baiquniy; Sayuti Sayuti; Anugrah Ramadhan Firdaus (COLLASE (Creative of Learning Students Elementary Education), 2018)
This study aims in general to improve the quality of natural science learning in elementary schools, so that knowledge of the material in the science subject of learning is not only in the form of concepts or only theoretically, but can be understood by students correctly, and can be applied to everyday life.This form of research is a classroom action research with the implementation model that is carried out in two cycles. Each cycle consists of 4 stages of planning, conducting, observing, analyzing and reflecting. The subjects of this study were at SD Rancakasumba year lesson 2017/2018. Technique of data analysis using interactive model consisting of 3 component of analysis that is data reduction, data presentation and verification.The results of the study can be seen from all sides who achieve mastery learning, namely students achieve a value of ≥ 70 increases, from 26.1% at the beginning to 65.2% in cycle I. After the action in cycle II, it increases again to 87%, or increased by 22% of completeness in cycle I. It was reflected in the entire cycle that can be done which allows students to improve student learning abilities in grade IV students of SDS 347 Rancakasumba 2017/2018 Academic Year.